PL.42 In Utero Transfer: 'It's Something You Have to Put Up with': A Qualitative Exploration of Its Impact on Families. (26th April 2013) - Porcellato, L; Masson, G; O'Mahony, F; Perkins, E; Jenkinson, S; Vanner, T; Cheshire, K
Abstract : In utero transfer (IUT) is a necessary facet of contemporary obstetrics, enabling the appropriate level of care for neonates (BAPM 2001). However, quantitative research has demonstrated that IUT can cause stress and anxiety and potentially impedes future pregnancies (Walker 2000). Although the impact of IUT on the families of expectant mothers has been assessed by Jackson et al, (2010) in a Scottish-wide audit, the issue has been largely ignored in England. It is important to examine IUTs from the service users' perspective, to ensure services are responsive to need and engender a positive birth experience. A small scale qualitative study was undertaken, to gain insight into the IUT process as experienced by women and their families, with a view to informing maternal care policy and practise. Semi structured interviews were carried out with 8 family members and 15 women who had been transferred into 2 tertiary obstetric centres in England between Aug 2010 and Dec 2011. Hour long digitally recorded interviews were conducted and thematically analysed using Nvivo 9. Results highlighted that the impact of IUT on families was primarily psychological, physical, social and financial; fathers were perceived to be the most affected by the process. There was resigned acceptance of the need for IUT but issues around lack of information about the transfer hospital, inflexible visiting hours and the inconvenience to visitors had a negative impact on families and need to be addressed, to improve the IUT experience for future service users. References: BAPM (Dec 2001) Standards for Hospitals Providing Neonatal and High Dependency Care (2 Edition). Jackson L, McLean D, Wilson AM, Skeoch C, An evaluation of the financial and emotional impact of in utero transfers upon families: a Scotland-wide audit. Infant, 6:2 (March 2010). Walker J (2000) Women's Experiences of Transfer from a Midwife-led to a Consultant-led Maternity unit in the UK During Late Pregnancy and Labour. JMWH 45: 2, 161–168.